PELATIHAN TEKNIK PEMBUATAN BUBUR KERTAS (PULP) DARI LIMBAH KORAN BEKAS BAGI SENIMAN DAN PENGRAJIN OGOH-OGOH DI DESA MELINGGIH, PAYANGAN, GIANYAR - Nindhia, T.G.T.; Surata, I. W.; Atmika, I. K. A.; Negara, D. N. K. P.; Komaladewi, A. A. I. A. S.; Sucipta, M; Suarnadwipa, I. N. (Buletin Udayana Mengabdi; Vol 13 No 2 (2014): Vol 13, No. 2 (2014), 2014)
The region of Melinggih in the sub district of Payangan, located at Gianyar regency in the province of Bali is supporting area for the tourist destination of Ubud and Sukawati. In this area, there are residing talented artist of fine arts, sculptor, dance and so called artist for ogoh-ogoh . Ogoh-ogoh is a local name for a created figure which will be carried together by group of peoples in celebration of Balinese new years. The creation method of ogoh-ogoh improve from time to time which is the important things is to obtain the good result and light to carry on. Recently the ogoh-ogoh is created by using styrofoam shaped by using knife. The price of styrofoam are expensive, easily broken, and easily burn therefore the ogoh-ogoh maker then explore how to make ogoh-ogoh by using pulp from paper or used newspaper. To support this challenge, the activity of training in making pulp from waste paper or used newspaper was conducted Keywords: Pulp, paper, ogoh-ogoh and training.